Analisis Makna al-‘Asr Studi Komparatif Terhadap Tafsir alMi?b?h dan Tafsir al-Sya’r?w? - Wely Dozan (el-'Umdah, 2019)
This paper aims to analyze the meaning of surah al-'Asr in both interpretations of contemporary figures, namely the interpretation of al-misbah and the interpretation of ash-sya'rawi in which the study has different interpretations both of the rules of language used to interpret aya-ayat al- The Qur'an. In addition, the two consultants have different styles and styles used in understanding the verses of the Qur'an. In this case the author positions himself as an analysis to review and describe and compare the results of the interpretation of the Qur'an in terms of methods, language and the second style of verse interpretation in the study of surah al-rAsr